Faktor Determinan Minat Masyarakat dalam Berwakaf Uang Reputasi Lembaga Wakaf dan Islamic Egalitarian - Ari Farizal Rasyid; Muhammad Dzulfaqori Jatnika; Yusep Rafiqi; Asep Saepulloh (Indonesian Journal of Islamic Economics and Business, 2023)
Indonesia has a large waqf potential but has not been optimized. This study aims to examine how the interest of cash waqf donation behavior in the people of West Java Province. This research develops previous theories by using a combination of reputation, integrity, trust, Islamic egalitarian, perceived ihsan, and Islamic religiosity variables. Hypothesis testing in this study uses the Structural Equation Model Partial Least Square approach. Respondents in this study were 250 people who live in West Java Province, are Muslim, and have a basic understanding of the concept of cash waqf. The results of this study are almost all the variables used in the study have a significant influence either directly or indirectly on the interest in waqf money, only the variable perception of ihsan has no influence on the interest in waqf money. This research only covers the people of West Java Province, in the future samples can be added that cover all of Indonesia or between countries. Waqf institutions also need to improve integrity, reputation, and public trust so that interest from the community.